Co-application of organic amendments and natural biostimulants on plants enhances wheat production and defense system under salt-alkali stress - Eman A. M. Zaghloul; El-Sayed A. Awad; Ibrahim R. Mohamed; Adel M. Abd El-Hameed; Di Feng; El-Sayed M. Desoky; Uthman Balgith Algopishi; Luluah M. Al Masoudi; Ahmed S. Elrys; Betty T. Mathew; Synan F. AbuQamar; Khaled A. El-Tarabily (Scientific Reports)
Abstract Soil alkalinity and salinity are major challenges to wheat production in arid regions. Eco-friendly amendments (organic matter and bio-stimulants) offer promising solutions, but their combined effects are underexplored. This study assessed the effects of organic amendments (vermicompost, compost, and chicken manure) combined with foliar bio-stimulants (licorice root, ginger rhizome, moringa leaf extract (MLE), and potassium humate) on wheat under salt and alkalinity stress. Organic amendments combined with bio-stimulants significantly improved wheat yields by enhancing chlorophyll content, proline levels, photosynthetic pigments, water uptake, and enzyme activities. Vermicompost outperformed compost and chicken manure in improving plant physico-biochemical properties. The combination of vermicompost and MLE was most effective in increasing plant height, leaf area, and photosynthetic rate by 97, 126, and 136%, respectively, while also enhancing catalase, peroxidase, and superoxide dismutase by 65, 97, and 185%, respectively. Consequently, this resulted in 64% increase in straw yield and 27% increase in grain yield compared to controls. Additionally, nutrient uptake (N, P, and K) significantly increased, while sodium uptake decreased. Integrating vermicompost with MLE can significantly enhance wheat productivity under abiotic stress, offering a sustainable solution to improve crop resilience in arid environments. Further research is required to understand the mechanisms and optimize bio-stimulant use in agriculture.